Does hyperoxic recovery during cross-country skiing team sprints enhance performance? - Hauser, A.; Zinner, C.; Born, D.-P.; Wehrlin, J. P.; Sperlich, B. (Medicine & Science in Sports & Exercise, 2014)
Purpose: This study aimed to determine the acute responses of breathing oxygen-enriched air during the recovery periods of a simulated 3 × 3-min cross-country skiing team sprint competition at simulated low altitude. Methods: Eight well-trained male endurance athletes performed two 3 × 3-min team sprint simulations on a double-poling ergometer at simulated altitude set at ~1800 m. During the recovery periods between the 3 × 3-min sprints, all the athletes inhaled either hyperoxic (FiO2 = 1.00) or hypoxic (FiO2 ~0.165) air in randomized and single-blind order. The mean total power output (Pmean tot) and the mean power output of each sprint (Pmean 1,2,3) were determined. Perceived exertion, capillary oxygen saturation of hemoglobin, partial pressure of oxygen, and blood lactate concentration were measured before and after all the sprints. Results: No differences in Pmean tot were found between hyperoxic (198.4 ± 27.1 W) and hypoxic (200.2 ± 28.0 W) recovery (P = 0.57, effect size [d] = 0.07). Pmean 1,2,3 (P > 0.90, d = 0.04-0.09) and RPE (P > 0.13, d = 0.02-0.63) did not differ between hyperoxic and hypoxic recovery. The partial pressure of oxygen (P < 0.01, d = 0.06-5.45) and oxygen saturation (P < 0.01, d = 0.15-5.40) during hyperoxic recovery were higher than those during hypoxic recovery. The blood lactate concentration was also lower directly after the third sprint (P = 0.03, d = 0.54) with hyperoxic recovery. Conclusion: Results indicate that trained endurance athletes who inhale 100% oxygen during recovery periods in a cross-country skiing team sprint at low altitude do not exhibit enhanced performance despite the improvement in the key physiological variables of endurance performance.